Analysis of the practice and the reasons for under documentation of body mass index and unintentional weight loss in adult hospitalized patients in Indian set up - Bajpai, Prashant K.; Singh, R. R.; Mehrotra, C. N.; Bhatia, Sanjiv (International Journal Of Community Medicine And Public Health, 2017)
Background: The present study analyzed the practice of documentation of BMI and history of unintentional weight loss in adult hospitalized patients on admission by the health care staff and the causes for their under documentation. Methods: A cross-sectional study was conducted among 600 healthcare workers, 150 duty medical officers and 450 nurses attending to adult hospitalized patients in both public and private hospitals of Lucknow, U.P., India and nearby districts. Information was collected on the basis of a self-administered questionnaire, on the practice of recording of weight, height, BMI and history of unintentional weight loss in past three months in patient records and also for the reasons for the under-documentation. Results: Only 54.16% of the staff admitted documenting BMI of the patients regularly in their case notes. Similarly, only 60% of the staff documented history of unintentional weight loss in past three months in patient case notes. Documentation was omitted more by nurses as compared to medical officers. The main reasons for under-documentation were work overload and time constraints, lack of training, confusion regarding responsibility and mistaken opinion for malnutrition screening. Conclusions: BMI and weight loss are often not recorded by health staff, more so by nurses. They need to be provided sufficient time to perform nutritional assessment of patient; moreover we should make them competent and delineate roles to them as well as develop a nutrition culture in our health facilities.